2019
DOI: 10.1142/s0219686719500203
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Surface Roughness for Inconel 718 in Blind Hole Drilling with Rotary Tool Electrode

Abstract: The research investigation reported on the effect of machining parameters on surface roughness (Ra) in electric discharge drilling of Inconel 718. Machining was done by using a copper tool electrode. Machining was conducted by considering different process parameters viz. tool diameter, discharge current, pulse on time, pulse off time, tool rotation and depth of hole. Optical surface profiler was used to measure surface roughness of drilled hole in work-piece. Design of experiment was created by Taguchi method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They achieved higher machining results on Inconel 718 Alloy through EDM. Kumar Rakesh et al [7] studied the EDM of Inconel 718 alloy with the ariance analysis method and found that the tool electrode rotation speed had the most significant influence on the surface roughness. The research of Tanjilul M et al [8] showed that with the increase of the depth of EDM processing superalloy Inconel 718, the processing efficiency decreased.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved higher machining results on Inconel 718 Alloy through EDM. Kumar Rakesh et al [7] studied the EDM of Inconel 718 alloy with the ariance analysis method and found that the tool electrode rotation speed had the most significant influence on the surface roughness. The research of Tanjilul M et al [8] showed that with the increase of the depth of EDM processing superalloy Inconel 718, the processing efficiency decreased.…”
Section: Introductionmentioning
confidence: 99%